Assessment of dietary intake of adolescent girls belonging to low socio economic status: a community based study from Lahore - Hassan, Fatima; Saleem, Shafya; Humayun, Ayesha (Progress in Nutrition, 2018)
Aim: To assess the dietary intake and dietary habits of adolescent girls belonging to low socio economic status to provide a baseline data for future intervention studies, a community based descriptive analytical study was conducted. Method: Unmarried adolescent girls, who had had their first menarche, were selected through convenience sampling. Informed verbal consent was obtained from the participants and their parents. Three days dietary recall was used to gather dietary data which was analyzed according to recommended servings of food groups in MY PLATE (USDA, 2011) and through modified Healthy Eating Index (HEI) scoring. Means and percentages were calculated and the data was analyzed through SPSS version 17. Result: All the adolescents were consuming less than recommended calories for their age. More than 50% of adolescent girls were taking less than half the required calories. About 74 % adolescents were skipping one meal or another at least four times a week. Majority of adolescent girls80% were not con-suming even a single serving from fruit group. The mean HEI score was also very low (29/100) and fell into poor category. A strong correlation r=0.88 was found between HEI scores and caloric intake. Conclusion: Dietary intake of adolescent girls belonging to low socio economic status is far from satisfactory which does not meet the recommended diet for this age group. Intervention strategies are needed to improve the dietary intake of adolescent girls so that their requirements of energy along with other nutrients are met.